Strategy disclosures by listed financial services companies: Signalling theory, legitimacy theory and South African integrated reporting practices - W. van Zijl; C. Wöstmann; W. Maroun (South African Journal of Business Management, 2017)
This paper investigates the current extent of social-, environmental- and economic- (SEE) related strategy disclosure of companies listed in the financial services sector of the Johannesburg Stock Exchange. It uses signalling and legitimacy theory to analyse the findings from a developed SEE strategy-related disclosure checklist.The paper finds social and environmental strategy-related disclosure is still secondary to economic strategy-related disclosures. This may be due to persistent focus on providers of financial capital and the need to perform financially. Further, the subsector's business model and how closely the subsector interacts with their customers is seen as a driver of social and environmental strategy-related disclosure to maintain their legitimacy and to reduce information asymmetry, reduce cost of capital and assure investors that these factors are being appropriately managed by the entity.Following from above, the banking, insurance and real estate subsectors presented the most strategy-related disclosure. This was linked to their high public accountability and daily interaction with customers, necessitating the need to manage their legitimacy and address adverse selection. The paper also proposes some areas for future research to understand the potential obstacles to incorporating social and environmental concerns into strategy and related disclosures.
Keywords: 650